2021
DOI: 10.4049/immunohorizons.2100038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity-Associated Chronic Inflammation on Peripheral Blood Immunophenotype Are Not Mediated by TNF in Female C57BL/6J Mice

Abstract: Chronic low-grade systemic inflammation in obesity contributes to the development and progression of aspects of metabolic syndrome. In obese male mice, expanded adipose tissue releases proinflammatory cytokines, including TNF, which promotes an increase in immature, proinflammatory, peripheral blood Ly-6C high monocytes. The aim of this study was to characterize how TNF alters circulating cellular immunity in female mice with diet-induced obesity. We initially quantified peripheral blood immune cells by flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…7 i ; see Figure S3 for other immune cell counts). Circulating monocytes are derived from bone marrow precursors, and HF diet promotes bone marrow myelopoiesis and egress of Ly6C high monocytes into circulation in non-pregnant females (31). Assessment of bone marrow in HF-fed dams compared to CTL-fed dams at E14.5 likewise showed elevated total quantities of leukocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 i ; see Figure S3 for other immune cell counts). Circulating monocytes are derived from bone marrow precursors, and HF diet promotes bone marrow myelopoiesis and egress of Ly6C high monocytes into circulation in non-pregnant females (31). Assessment of bone marrow in HF-fed dams compared to CTL-fed dams at E14.5 likewise showed elevated total quantities of leukocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We now also report significant modifications in blood immune cell composition in HF-fed dams at E14.5, but not E18.5. We have previously shown that non-pregnant female mice with diet-induced obesity have increased numbers of circulating TNF-producing inflammatory Ly6C high monocytes (31). Here we similarly show that Ly6C high monocytes were increased in HF-fed dams at mid-but not late gestation compared to CTL dams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has become a fast-growing global health problem in today's society, which can have a major negative impact on life. There is evidence that obesity affects the immune system (4)(5)(6), and an association between obesity and chronic inflammation has been demonstrated (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Changes to monocyte-derived macrophage phenotype and function may also occur within intestinal tissues under conditions of the systemic, low-grade and chronic inflammation that is characteristic of obesity (Hotamisligil, 2017). Obesity increases circulating Ly6C high monocytes (Breznik et al ., 2018; Breznik et al ., 2021a), which differentiate into pro-inflammatory macrophages within metabolic tissues like adipose (Weisberg et al ., 2003; Kanda et al ., 2006). While it has been reported that there is an accumulation of pro-inflammatory macrophages within the colon in obesity (Kawano et al ., 2016), which could contribute to observations of obesity-associated increases in gut permeability (Cani et al ., 2007; Cani et al ., 2008; Johnson et al ., 2015; Kawano et al ., 2016), there is a lack of consensus across published research (Garidou et al ., 2015; Johnson et al ., 2015; Hong et al ., 2017; Luck et al ., 2019; Rohm et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%